KOMUNIKASI RISIKO HIV DAN AIDS BAGI KELOMPOK REMAJA GAY DI JAKARTA - Slamet Widadi (Jurnal Visi Komunikasi, 2017)
Current information related knowledge of HIV and AIDS is not yet a priority need and not fully accessible to teenagers. They prefer the latest information and modern related to life style or lifestyle. The focus of this research is "How Worker Outreach activities Inter Medika Foundation in communicating HIV and AIDS for" Gay Teen "in Jakarta?". The purpose of this study one of them is "researchers can find out about the activities of the Outreach Worker Foundation for Inter Medika in communicating HIV and AIDS for Gay Teens in Jakarta, As this study using the case study method, with the approach of constructivism paradigm, and in the data collection of researchers using observation and depth interview to the informant. The results of this study to discuss the introduction of the situation and the problems encountered, use of media, communications content, process communication activities, implementation and monitoring and evaluation. This study concludes that the communication activities conducted by Outreach Worker Inter Medika Foundation emphasizes the provision of information through online media (Internet Outreach) and direct outreach activities (face to face), because it is very effective to improve the performance of programs that run today.Pengetahuan terkait HIV dan AIDS saat ini belum menjadi kebutuhan prioritas dan tidak dapat diakses sepenuhnya oleh remaja. Mereka lebih menyukai informasi terbaru dan modern yang terkait dengan gaya hidup atau gaya hidup. Fokus penelitian ini adalah "Bagaimana Kegiatan Outreach Pekerja Antar Medika Foundation dalam mengkomunikasikan HIV dan AIDS untuk" Remaja Gay "di Jakarta?". Tujuan dari penelitian ini salah satunya adalah "peneliti dapat mengetahui tentang kegiatan Outreach Worker Foundation untuk Inter Medika dalam mengkomunikasikan HIV dan AIDS untuk Remaja Gay di jakarta, Seperti penelitian ini menggunakan metode studi kasus, dengan pendekatan konstruktivisme Paradigma, dan dalam pengumpulan data peneliti menggunakan observasi dan wawancara mendalam kepada informan. Hasil penelitian ini untuk membahas pengenalan situasi dan permasalahan yang dihadapi, penggunaan media, konten komunikasi yang dikirim, kegiatan komunikasi, pelaksanaan dan pemantauan dan evaluasi dalam mengkomunikasikan HIV dan AIDS untuk Remaja Gay di Jakarta. Penelitian ini menyimpulkan bahwa kegiatan komunikasi yang dilakukan oleh Outreach Worker Inter Medika Foundation menekankan penyediaan informasi melalui media online (Internet Outreach ) Dan kegiatan penjangkauan langsung (face to face), karena sangat e Ffective untuk meningkatkan kinerja program yang dijalankan saat ini.